CURRENT STATE AND ASSESSMENT OF THE LANDSCAPE-ECOLOGICAL CONDITIONS OF THE NORTHERN FERGANA FOOTHILL REGION (Scientific journal of the Fergana State University, 2026)
This scientific study provides a systematic analysis of the landscape-ecological conditions and geoecological situation of the Northern Fergana foothill region. The research examines the anthropogenic transformations occurring in geosystems as a result of human economic activities and their impact on the stability of the natural environment. Based on Professor A.A. Rafiqov’s theoretical concept of the geoecological situation, a comprehensive set of assessment criteria has been developed, including four main aspects: the state of geosystems, the ecological condition of natural components, public health, and the level of anthropogenic pressure. Using satellite data derived from ArcGIS software (NDVI, ArcMonitoring, and Hotspot modules), a system of indicators was constructed to determine the degree of landscape transformation. The results indicate that in areas where more than 50% of geosystems have been altered, ecological stability has sharply declined, and signs of environmental crisis have become evident. Furthermore, increased anthropogenic pressure has been shown to directly and negatively affect public health. The study concludes that rational use of natural resources, mitigation of degradation processes, and implementation of scientifically grounded measures are essential to ensure ecological sustainability in the region